PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA SUNGAI BULUH KECAMATAN BUNUT KABUPATEN PELALAWAN - hernimawati, hernimawati; nielwaty, elly; aliyana, aliyana (Jurnal Niara, 2018)
The purpose of this study was to find out and analyze community participation and analyze barriers to community participation in the development of Sungai Buluh Village, Bunut District, Pelalawan District. The method used in this research is qualitative descriptive. In this study the analysis unit was the community involved in the development in Sungai Buluh village. The results of the study found that not many people participated in development because most people were not aware of the activities. Suggestions from this study In order to achieve development success in increasing community participation, the socialization program should be maximized again in meetings so that many people attend the village planning meetings held